Modulating Dye Aggregation by Incorporation into 1D‐MgAPO Nanochannels1. Issue 30 (18th June 2013) - Martínez‐Martínez, Virginia; García, Raquel; Gómez‐Hortigüela, Luis; Pérez‐Pariente, Joaquín; López‐Arbeloa, Iñigo
Abstract The fluorescing dye Pyronine Y has been incorporated by crystallization inclusion into three different one‐dimensional microporous aluminophosphate host materials. A computer‐aided rational choice of the framework of the host material made it possible to modulate the aggregation state of the guest dye molecules. Undesirable H‐type dimers of Pyronine Y are included within the large channels of the AFI structure, which allow the inclusion of any of the aggregated species of the dye. Density functional theory (DFT) calculations show that H‐type aggregate formation is suppressed within the ATS framework. Experimental results indicate that red‐emissive J‐type aggregates are formed instead, offering a one‐directional, organized, multicolour emission system that is interesting for energy transport. Complete suppression of aggregation is achieved by the inclusion of Pyronine Y within the AEL‐type structure, due to its particular topology and channel dimensions This results in a highly fluorescent hybrid system with extraordinarily preferential alignment of the chromophores. Here, we report experimental evidence and modelling insights for how the "cage effect" of the nanochannels can tune the optical properties of the hybrid composite material by influencing the aggregation state of the dye.